DATA MINING TECHNIQUES FOR SOFTWARE EFFORT ESTIMATION TO IMPROVE COST EFFICIENCY (International Journal of Engineering and Computer Science, 2017)
Software Cost Estimation can be described as the process of predicting the most realistic effort required to complete a software project. Due to the strong relationship of accurate effort estimations with many crucial project management activities, the research community has been focused on the development and application of a vast variety of methods and models trying to improve the estimation procedure. The rapidly increased need of large-scaled and complex software systems leads managers to settle SEE (software effort estimation) as one of the most vital activities that is closely related with the success or failure of the whole development process. Data mining tool is used for selecting a subset of highly predictive attributes such as project size, development, and environment related attributes, typically a significant increase in effort estimation accuracy can be obtained.